Organizacja imprez cyklicznych jako jedna z istotnych form działań promocyjnych miast - Zawadzki, Piotr (Organization of Cyclical Events as the form of Towns' Promotional Activities, 2005)
The article presents opportunities for using cyclical events by the local self-governments, in order to create positive image of the town. The organization of such events was pointed to as the public relations type of activity, which plays the role of keeping up the awareness and positive attitudes. Polish towns utilise the organization of regularly held events in their promotional activities. The article describes basic features and presents advantages resulting from the organization of such events. The author of the hereby article has presented the event "Wrzesień Jeleniogórski" ('September in Jelenia Góra') as the example of an even held on a regular basis which is, at the same time, the biggest event taking place in Jelenia Góra town.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 253-263